Faktor yang Berhubungan dengan Niat untuk Melakukan Vaksinasi COVID-19 di Kabupaten Bekasi - Faiz, Jihan Fadilah; Hamzens, Muhammad Farid (Journal of Religion and Public Health, 2022)
COVID-19 vaccination is one way to reduce the pandemic which will be given to 70% of the population to achieve herd immunity, but there are still many rejections from the community and the cause needs to be known. This can be predicted with the variable of intention to carry out the COVID-19 vaccine and its factors so that it can be used as consideration in achieving the targets that have been set. The purpose of this study was to determine the factors associated with the intention to vaccinate against COVID-19 with the Theory of Planned Behavior approach. This study used a cross sectional analytic study design with a volunteer sampling technique. Data collection using online and offline questionnaires were collected from 15 February to 28 March 2021. The questionnaire contained questions regarding the characteristics of respondents, attitudes to vaccinating COVID- 19, subjective norms, perceptions of behavioral control and intentions to vaccinate against COVID-19. A total of 108 respondents with sample criteria not registered as a participant in the COVID-19 vaccination, who have never been vaccinated against COVID-19, aged 18 years and domiciled in Bekasi Regency. Univariate and bivariate (chi-square) analysis were used to analyze the data.Most of them are 18-35 years old (53.7%) which are dominated by women (77.8%) with the last education being SLTA (63%). As many as 79.6% of respondents have a positive attitude to vaccinate COVID-19, as many as 64.8% of respondents have positive subjective norms and there is not much difference between perceptions of positive (57.4%) and negative behavior control (42.6%). Respondents who have the intention to vaccinate against COVID-19 are 58.3%. There is a relationship between the attitude to vaccinate against COVID-19 (p- value=0.010) and subjective norm (p-value=0.040) with intention to vaccinate against COVID-19. Conclusion: Intention to vaccinate against COVID-19 is still low. It is necessary to provide education regarding the importance of COVID-19 vaccination by utilizing social media as a means of education.Keyword: intention of COVID-19 vaccine, attitude toward COVID-19 vaccine, subjective norms, perceived behavioral control.AbstrakVaksinasi COVID-19 merupakan salah satu cara dalam menurunkan pandemi yang akan diberikan kepada 70% penduduk untuk mencapai herd immunity, namun masih banyak penolakan dari masyarakat yang perlu diketahui penyebabnya. Hal ini dapat diprediksi dengan variabel niat untuk melakukan vaksinasi COVID-19 serta faktornya sehingga dapat dijadikan sebagai bahan pertimbangan dalam mencapai target yang telah ditetapkan. Tujuan penelitian ini adalah untuk mengetahui faktor yang berhubungan dengan niat untuk melakukan vaksinasi COVID-19 dengan pendekatan Theory of Planned Behavior. Penelitian ini menggunakan desain studi analitik cross sectional dengan teknik sampel volunteer sampling. Pengumpulan data menggunakan kuesioner online dan offline yang dikumpulkan dari 15 Februari-28 Maret 2021. Kuesioner berisi pertanyaan mengenai karakteristik responden, sikap untuk melakukan vaksinasi COVID-19, norma subjektif, persepsi kontrol perilaku dan niat untuk melakukan vaksinasi COVID-19. Sebanyak 108 responden dengan kriteria sampel yang belum terdaftar sebagai peserta vaksinasi COVID-19, pernah divaksinasi COVID-19, berusia ≥18 tahun dan berdomisili di Kabupaten Bekasi. Analisis univariat dan bivariat (chi-square) digunakan untuk menganalisis data. Sebagian besar berusia 18-35 tahun (53,7%) yang didominasi oleh perempuan (77,8%) dengan pendidikan terakhir adalah SMA (63%). Sebanyak 79,6% responden memiliki sikap positif untuk melakukan vaksinasi COVID-19, sebanyak 64,8% responden memiliki norma subjektif positif dan tidak jauh berbeda antara persepsi kontrol perilaku positif (57,4%) dan negatif (42,6%). Responden yang memiliki niat untuk melakukan vaksinasi COVID-19 sebanyak 58,3%. Terdapat hubungan antara sikap untuk melakukan vaksinasi COVID-19 (p-value=0,010) dan norma subjektif (p-value=0,040) dengan niat untuk melakukan vaksinasi COVID-19. Niat untuk melakukan vaksinasi COVID-19 masih rendah. Perlu mengadakan edukasi terkait pentingnya vaksinasi COVID-19 dengan memanfaatkan media sosial sebagai sarana edukasi.Kata Kunci: niat untuk melakukan vaksinasi COVID-19, sikap untuk melakukan vaksinasi COVID-19, norma subjektif, persepsi kontrol perilaku